Relationship between National Health Insurance Ownership and Compliance with Access to Health Services for Patients with Severe Mental Disorders (PSMD) “Pasung” in Blitar Regency, Indonesia - Dhimas Anggi Septiansyah; Emi Wuri Wuryaningsih; Fitrio Deviantony (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
Patients with Severe Mental Disorders (PSMD)